Proportional-resonant based control strategy for grid-connected packed-E cell inverters with Lyapunov filter-based PLL - Biricik, Samet; Komurcugil, Hasan; Ahmed, Hafiz; Sharifzadeh, Mohammad; Mehrasa, Majid; Al-Haddad, Kamal (Inst Engineering Technology-Iet, 2023)
A proportional-resonant (PR)-based current control strategy for grid-connected packed-E cell (PEC) inverter is presented. Unlike the existing control strategies, which are based on proportional-integral controller, developed for packed-U cell and PEC inverters, the proposed PR-based control strategy achieves zero steady-state error in the grid current. Furthermore, it eliminates the necessity of employing the control loop for regulating the dc capacitor voltages. Also, the grid current synchronization is achieved by using a Lyapunov filter-based phase locked loop (PLL). The consequence of using Lyapunov filter-based PLL is that sinusoidal synchronization signal can be extracted from the distorted grid voltage. The performances of the proposed control strategy under steady-state, load variation and non-ideal grid voltage are investigated on a laboratory-scale experimental prototype. It is reported that the control of both dc- and ac-side variables of the system are accomplished.
Keywords: Operation; Pwm